Tales From Another World - Veglio, Maurizio (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
At the Human Rights and Migration Law Clinic (HRMLC), established at the International University College of Turin, narratives from asylum seekers are conveyed by clinical students into written legal memos aimed at supporting claims for international protection. Throughout the process the former become (often unconscious) authors, while the latter are the medium – pens, keyboards and lenses – shaping words into a script. Resulting legal papers encapsulate life diaries and chronicles of violence, obsession and death, a more-than-contemporary form of literature mingling history, drama and legal storytelling.